SECONDARY BRAIN INJURY - Basmatika, Ida Ayu (E-Jurnal Medika Udayana; vol 2 no3 (2013):e-jurnal medika udayana, 2013)
Secondary brain injury is a condision that occurs at some times after the primary impact and can be largely prevented and treated. Most brain injury ends with deadly consequences which is caused by secondary damage to the brain. Traumatic brain injured still represents the leading cause of morbidity and mortality in individuals under the age of 45 years in the world. The classification of secondary brain injured is divided into extracranial and intracranial causes. The cause of extracranial such as hipoxia, hypotensi, hyponatremia, hypertermia, hypoglycemia or hyperglycemia. The cause of intracranial such as extradural, subdural, intraserebral, intraventrikular, dan subarachnoid hemorrhage. Beside that secondary injury can also be caused by edema and infection. Post-traumatic cerebral injured is characterized by direct tissue damage, impaired regulation of cerebral blood flow (cerebral blood flow / CBF), and disruption of metabolism. Manifestations of secondary brain injured include increased intracranial pressure, ischemic brain damage, cerebral hypoxia and hypercarbi, as well as disruption of cerebral autoregulation. The first priority is to stabilize the patient's cervical spine injury, relieve and maintain airway, ensure adequate ventilation (breathing), and making venous access for fluid resuscitation pathways (circulation) and assessing the level of awareness and disability. This steps is crucial in patients with head injured to prevent hypoxia and hypotension, which is the main cause of secondary brain injury.
Keywords: secondary brain injury, intracranial, extracranial